PENERAPAN ARTIFICIAL INTELLIGENCE DALAM CUSTOMER RELATIONSHIP MANAGEMENT: SUATU TINJAUAN LITERATUR - Tan, Rivaldo; Setiawan, Alexander (Penerbit Lafadz Jaya, 2026)
Artificial Intelligence (AI) adoption in Customer Relationship Management (CRM) has transformed customer engagement paradigms globally, yet organizational implementation paradoxes persist. This systematic literature review synthesized state-of-the-art knowledge on AI-CRM applications through qualitative content analysis of peer-reviewed articles published between 2021-2025 using PRISMA 2020 guidelines. The study employed purposive sampling across six major academic databases (Scopus, Web of Science, ProQuest, Google Scholar, SSRN, and local Indonesian repositories), with hybrid coding approach integrating deductive-inductive methods. An estimated 50-100 studies were projected for inclusion from 1,500-2,500 initial records. Results identified five primary mechanisms through which AI-CRM enhances business effectiveness: personalized customer experiences, real-time decision-making, enhanced service efficiency, improved customer segmentation, and proactive churn management. Organizations implementing AI-CRM report 29% average sales increases and ROI reaching 245%, yet 70% report unachieved direct performance benefits. Conclusions indicate that success depends predominantly on organizational factors, data governance, and ethical considerations rather than technology capabilities alone. Recommendations emphasize holistic implementation approaches integrating robust change management, ethical AI frameworks, and capability building, particularly crucial for Indonesia's SME-dominant context.